The Management Role of School Administrative Personnel in Improving Operational Efficiency - Wi'am, Atief Aisyil; Yaqien, Nurul; Triwiyanto, Teguh (Universitas Negeri Malang, 2024)
This study analyzes the management role of school administrative personnel in improving operational efficiency. Results show that effective documentation and financial management increase transparency and support decision-making. In addition, efficient timetabling helps maximize the use of time and resources and enables students to engage in a variety of activities. Good resource management creates a conducive learning environment while effective communication between the school, parents and the community strengthens support for the education program. The implementation of information technology and data-driven management, such as the use of ICT and Lean Six Sigma, is proven to significantly improve the efficiency of school operations. The high quality of administrative services has a positive impact on student and parent satisfaction, contributing to the school's reputation. This study concludes that strengthening the role of administrative personnel is crucial to achieving better educational goals and recommends professional training as a priority for school management.